Os processos eleitorais na América Latina (2005-2006) - Avila, Carlos (Sociedade e Estado, 2011)
SANTANDER, Carlos Ugo; PENTEADO, Nelson. Os processos eleitorais na América Latina (2005-2006). Brasília: LGE, 2008. 398 p. ISBN: 978-85-7238-333-2.